2021
DOI: 10.1155/2021/9987097
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacological Activities of Berberine in Diabetes Mellitus Treatment

Abstract: Traditional Chinese medicine (TCM) has good clinical application prospects in diabetes treatment. In addition, TCM is less toxic and/or has fewer side effects and provides various therapeutic effects. Berberine (BBR) is isolated as the main component in many TCM kinds (e.g., Rhizoma Coptidis and Berberidis Cortex). Furthermore, BBR can reduce blood sugar and blood fat, alleviate inflammation, and improve the state of patients. Based on the recent study results of BBR in diabetes treatment, the BBR pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 126 publications
(149 reference statements)
0
40
0
Order By: Relevance
“…Berberine exerts superior therapeutical effects on the vascular diseases, such as atherosclerosis; however, its effects are limited in clinic due to poor oral absorption and low bioavailability ( Han et al, 2021b ). Previous research has reported that the absolute bioavailability of berberine is 0.37% when administered in a single oral administration (48.2, 120, or 240 mg/kg body weight) in rats ( Feng et al, 2021 ).…”
Section: Pharmacokinetics Of Berberinementioning
confidence: 99%
See 2 more Smart Citations
“…Berberine exerts superior therapeutical effects on the vascular diseases, such as atherosclerosis; however, its effects are limited in clinic due to poor oral absorption and low bioavailability ( Han et al, 2021b ). Previous research has reported that the absolute bioavailability of berberine is 0.37% when administered in a single oral administration (48.2, 120, or 240 mg/kg body weight) in rats ( Feng et al, 2021 ).…”
Section: Pharmacokinetics Of Berberinementioning
confidence: 99%
“…However, due to its low in vivo bioavailability, exploring methods that increase the concentration of berberine in blood is key to improving its usefulness in this context. Although intravenous administration provides a direct approach that may improve the bioavailability of berberine, this can lead to serious side effects including respiratory arrest ( Han et al, 2021b ). Therefore, berberine is often administered orally in clinic.…”
Section: Pharmacokinetics Of Berberinementioning
confidence: 99%
See 1 more Smart Citation
“…Berberine is widely used to treat diabetes mellitus, and its mechanism probably consists of inhibiting hepatic gluconeogenesis and inducing hyperglycolysis and insulin sensitivity. 124 On the other hand, sophoridine is the focus of anti-tumor research, particularly malignant trophoblastic tumors. Many experimental studies have confirmed that berberine is metabolized rapidly in vivo, primarily by the liver and intestinal flora, and its content and structure change after metabolism.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Many experimental studies have confirmed that berberine is metabolized rapidly in vivo, primarily by the liver and intestinal flora, and its content and structure change after metabolism. 124 In contrast, research shows that sophoridine is metabolized primarily through urine excretion as a prototype of the human kidney. 8 , 98 Still, the difference in LD 50 between sophoridine and berberine (65.19 vs 57.6 mg/kg) by intraperitoneal injection is miniscule.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%